Optic neuropathies as an interdisciplinary subject of research - Sheremet, N L; Eliseeva, D D; Bryukhov, V V; Kalashnikova, A K; Kaloshina, A A; Murakhovskaya, Yu K; Krylova, T D; Tsygankova, P G; Zakharova, M N (Vestnik oftal'mologii, 2023)
Despite the wide range of clinical, instrumental and laboratory methods used in modern ophthalmology, the problem of diagnosing optic neuropathy and identifying its etiology remains relevant. A complex multidisciplinary approach involving various specialists is required in the differential diagnosis of immune-mediated optic neuritis, for example in multiple sclerosis, neuromyelitis optica spectrum disorder, and MOG-associated diseases. Of special interest is differential diagnosis of optic neuropathy in demyelinating diseases of the central nervous system, hereditary optic neuropathies and ischemic optic neuropathy. The article presents a summary of scientific and practical results of differential diagnosis of optic neuropathies with various etiologies. Timely diagnosis and early therapy start reduces the degree of disability in patients with optic neuropathies of different etiologies.